IND-2, a pyrimido[1″, 2″:1, 5]pyrazolo[3, 4-b]quinoline derivative, circumvents multi-drug resistance and causes apoptosis in colon cancer cells. Issue 3 (1st February 2015) - Karthikeyan, Chandrabose; Lee, Crystal; Moore, Joshua; Mittal, Roopali; Suswam, Esther A.; Abbott, Kodye L.; Pondugula, Satyanarayana R.; Manne, Upender; Narayanan, Narayanan K.; Trivedi, Piyush; Tiwari, Amit K.
Graphical abstract: Abstract: Naturally occurring condensed quinolines have anticancer properties. In efforts to find active analogues, we designed and synthesized eight polycyclic heterocycles with a pyrimido[1″, 2″:1, 5]pyrazolo[3, 4- b ]quinoline framework (IND series). The compounds were evaluated for activity against colon (HCT-116 and S1-MI-80), prostate (PC3 and DU-145), breast (MCF-7 and MDAMB-231), ovarian (ov2008 and A2780), and hepatocellular (HepG2) cancer cells and against non-cancerous Madin Darby canine kidney (MDCK), mouse embryonic fibroblast (NIH/3T3), and human embryonic kidney cells (HEK293).IND -2, a 4-chloro-2-methyl pyrimido[1″, 2″:1, 5]pyrazolo[3, 4- b ]quinoline, exhibited more than ten-fold selectivity and potent cytotoxic activity against colon cancer cells relative to the other cancer and non-cancer cells. With five additional colon cancer cell lines (HT-29, HCT-15, LS-180, LS-174, and LoVo), IND -2 had similar cytotoxicity and selectivity, and sub-micromolar concentrations caused changes in the morphology of HCT-116 and HCT-15 cells.IND -2 did not activate the transactivating function of the pregnane X receptor (PXR), indicating that it does not induce PXR-regulated ABCB1 or ABCG2 transporters. Indeed, IND -2 was not a substrate of ABCB1 or ABCG2, and it induced cytotoxicity in HEK293 cells overexpressing ABCB1 or ABCG2 to the same extent as in normal HEK293 cells.IND -2 was cytotoxic to resistant colon carcinoma S1-MI-80 cells, approximately three- and five-fold more than SN-38 and topotecan, respectively. In HCT-116 colon cancer cells, IND -2 produced concentration-dependent changes in mitochondrial membrane potential, leading to apoptosis, and sub-micromolar concentrations caused chromosomal DNA fragmentation. These findings suggest that, by increasing apoptosis, IND -2 has potential therapeutic efficacy for colorectal cancer.